DIALOG BIMBINGAN DAN KONSELING PERSPEKTIF AL-ASR AYAT 3 - Marsal Yunas Muliadi; Irman Irman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The study of dialogue in counseling is the main factor in the counseling process which contains positive values that are transferred to clients. The purpose of this study is to describe dialogue in counseling guidance that will be discussed in accordance with the perspective of Al –Asr Paragraph 3. The research method used in this research is the study of literature. The results of the study show that dialogue in guidance and counseling is in accordance with the principles in Al-Asr verse 3, namely "Except for those who believe and do good deeds and advise advising them to obey the truth and advice advising them to remain patient." Referring to the purpose of Islamic guidance and counseling is to help clients to create himself becomes fully human in order to reach the world and the hereafter